The impact of world evaluation standards on assessment of agricultural property in Ukraine - Avramchuk, B. (Land Management, Cadastre and Land Monitoring, 2017)
Analyzed the basic principles of the assessment of agricultural property within the majorworld evaluation standards and their impact on evaluation standards in Ukraine..Keywords: real estate, property, agriculture, property appraisal, assessment standards.